2022
DOI: 10.4103/jllr.jllr_17_22
|View full text |Cite
|
Sign up to set email alerts
|

Residual Amputee Limb Segment Lengthening

Abstract: Aims: This study aimed to systematically review the indications, techniques, complications, and insights identified for lower extremity residual amputee limb segment lengthening. Methods: Searches in PubMed, Google Scholar, Ovid Medline, Ovid Embase, and the Journal of Limb Lengthening and Reconstruction were performed using terms including “amputee,” “residual limb,” and “stump” combined with “lengthening,” “distraction,” “histogenesis,” “osteogenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Alternatives include socket modification, bone lengthening and/or soft-tissue contouring 13 , Krukenberg-type reconstructions 14 , or accepting the situation. An alternative implant is a screw-type osseointegration implant.…”
Section: Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatives include socket modification, bone lengthening and/or soft-tissue contouring 13 , Krukenberg-type reconstructions 14 , or accepting the situation. An alternative implant is a screw-type osseointegration implant.…”
Section: Alternativesmentioning
confidence: 99%
“…or to create targets for transcutaneous myoelectrodes, targeted muscle reinnervation or a regenerative peripheral nerve interface procedure could be performed following exposure. Alternatives: Alternatives include socket modification, bone lengthening and/or soft-tissue contouring 13 , Krukenbergtype reconstructions 14 , or accepting the situation. An alternative implant is a screw-type osseointegration implant.…”
mentioning
confidence: 99%
“…Larger-diameter cobalt-chromium and steel implants were found to have greater resistance to bending forces than titanium nails. Finally, in a systematic review of limb segment lengthening in amputees, Chavan et al concluded that, despite potential complications such as segment overlengthening, the potential for improved prosthetic fitting and use makes this a beneficial option in this group of patients 46 .…”
Section: Limb Lengtheningmentioning
confidence: 99%
“…5) and dramatically improve prosthesis control. [49][50][51] Patient and system factors are potentially more pronounced with amputation. Patients without the ability to receive regular prosthetic care may comparatively benefit from "heroic" attempts at limb salvage.…”
Section: Optimize Amputationsmentioning
confidence: 99%